Analysis of IPTV services in LAN/WLAN networks - Sindhu, Ritu (International Journal of Computer Sciences and Engineering, 2025)
The Internet Protocol Television (IPTV) is becoming one of the most promising applications over next generation networks. With the recent released of IEEE 802.16d/e, it is capable ensuring high bandwidths and low latency and suitable for delivering multimedia services. Importance of perceptual quality has arisen as one of the major issues to successfully deploy IPTV services. Therefore, guaranteeing a certain level of network QoS is well and widely understood, but it is much more important to notice perceptual quality as perceived by the user. In this paper, we have designed a new network consists of FTP server and HTTP server which are connected to four subnets and IP cloud. We have evaluated the performance of this network and quality of service considering the parameters throughput, delay, load and data dropped.